The Legal Regulation of Neighbourly Water use in Ukraine: Development Prospects - Ihor Myronenko (Vasyl Stefanyk Precarpathian National University, 2018)
The article is devoted to some questions of the legal adjusting of neighbourliness relations. Neighbourly water use should be defined as the use of water resources aimed at meeting the needs of owners or tenants of neighbouring land parcels. The regulation of neighbourly water use has historically been an inseparable part of neighbour law. Regulations of this kind were contained in many historically significant Ukrainian legal documents, including "The Statutes of the Grand Duchy of Lithuania". Currently, the regulation of the use of water resources mainly comes under the sphere of public law. Consequently, the current Land Code of Ukraine does not contain regulations of this kind. Nevertheless, a study of international legislation and regulation policies on neighbourly relations emphasizes the necessity to legislate on the private aspects of neighbourly water use. The findings of the study has made it possible to formulate the proposals aimed at improving the current legislation on this issue.